Can The Effectiveness of Whistleblowing System and Ewuh Pakewuh Culture Influence Fraud Disclosure? - Ratna Sari, Maria Mediatrix; Sustriani, Putu Nokia; Suprasto, Herkulanus Bambang (Jurnal Ilmiah Akuntansi dan Bisnis, 2023)
This study aims to examine the effect of the effectiveness of the whistleblowing system and the ewuh pakewuh culture on fraud disclosure. One hundred forty-eight internal auditors from Provincial and Regency Inspectorates throughout Bali are used as a sample in this study. This study uses a saturated sampling technique. Collecting data techniques by using questionnaires. Hypothesis analyzed using Structural Equation Model (SEM). The analysis results show that the whistleblowing system's effectiveness positively affects fraud disclosure, and the ewuh pakewuh culture negatively affects fraud disclosure. This research is expected to be an essential input for increasing the internal supervision of local government inspectorates, especially the Bali Regional Inspectorate, which includes the Provincial Inspectorate and Regency or City Inspectorate throughout Bali. Keywords: fraud disclosure, whistleblowing system, and ewuh pakewuh   culture